PREDICTION OF RISK FACTORS OF LATERAL LYMPH NODE METASTASIS IN RECTAL CANCER - A. A. Zakharenko; M. A. Belyaev; A. N. Morozov; I. N. Danilov; A. A. Statsenko; A. A. Trushin; O. A. Ten; K. N. Vovin (Вестник хирургии имени И.И. Грекова)
Standard methods of diagnostics haven’t got a proper sensitivity and specificity concerning assessment of regional nodal involvement in case of rectal cancer. Therefore it is necessary to look for new method of diagnostics, detect risk factors and unfavorable prognosis in relation to lateral lymph node metastasis. At the same time, there should be a differentiated approach to the choice of therapeutic management in rectal cancer. Investigation of variability of blood supply of the rectum could be an additional method of diagnostics in rectal cancer.